EDUCATION AND LEARNING IN BIOMECHANICS: ENHANCING ATHLETES' CONFIDENCE THROUGH Q-ANGLE INTERVENTION - Ginanjar, Moch Septian Abdul; Fitri, Mustika; Williyanto, Septian; Apriady, Hilmy (JETL (Journal of Education, Teaching and Learning), 2024)
Futsal's popularity is growing, with over 12 million registered players globally, including a rising number of female players. Despite its growth, futsal poses significant injury risks, especially to the lower extremities, which can impact athletes' performance and self-efficacy. This study aims to explore the effect between the knee Q-angle intervention on self-efficacy in professional female futsal players. This observational and correlational study involved 11 athletes from the professional futsal club Muara Enim United in Indonesia. The procedure of this study participants trained regularly for at least 2 hours per week and were excluded if injured or had prior lower extremity surgery. The study measured Q-angles and self-efficacy using the Athlete Self-Efficacy Scale before and after league matches over 14 days. Data were analyzed using paired sample t-tests to assess changes in self-efficacy. Normality tests confirmed that pretest and posttest data were normally distributed. Descriptive statistics indicated a mean pretest score of 43.33 and a posttest score of 36.31. Paired sample t-tests revealed a significant decrease in self-efficacy post-intervention (p=0.017). The significant reduction in posttest scores suggests the intervention was less effective in enhancing self-efficacy. This decline highlights the need for improved intervention strategies to bolster self-efficacy in female futsal athletes. Self-efficacy is crucial for performance and injury management, as it influences motivation, stress management, and persistence in athletes. This study underscores the necessity for rigorous evaluation of interventions aimed at improving self-efficacy among professional female futsal players. Understanding the relationship between the knee Q-angle and self-efficacy can inform the development of better training and injury prevention programs, ultimately enhancing athletes' well-being and performance. Future research should address external variables and use larger sample sizes to validate these findings.